Discourses of Biratā (Bravery) and Shānti (Peace) in School Level Nepalese textbooks - Aryal, Deepak (Bodhi: An Interdisciplinary Journal, 2010)
DOI: 10.3126/bodhi.v2i1.2865 Bodhi Vol.2(1) 2008 p.89-116